The synergic role of collagen and citrate in stabilizing amorphous calcium phosphate precursors with platy morphology. (February 2017) - Delgado-López, José Manuel; Bertolotti, Federica; Lyngsø, Jeppe; Pedersen, Jan Skov; Cervellino, Antonio; Masciocchi, Norberto; Guagliardi, Antonietta
Graphical abstract: Abstract: Bioinspired in vitro collagen mineralization experiments have been performed in the presence of citrate and the combined role of the two bone organic matrix components in controlling mineral formation was investigated for the first time. Mineralized and non-mineralized collagen fibrils have been in depth characterized by combining small- and wide-angle X-ray scattering (SAXS/WAXS) techniques with Atomic Force Microscopy (AFM) imaging. A synergic effect of collagen and citrate in driving the formation of long-term stable amorphous calcium phosphate (ACP) nanoparticles with platy morphology was found. AFM images on mineralized collagen fibrils revealed that some of the ACP nanoparticles were deposited on the intramolecular nanoscopic holes of collagen fibrils. Statement of Significance: Citrate is an important component of the bone organic matrix but its specific role in bone mineralization is presently unclear. In this work, bioinspired in vitro collagen mineralization experiments in the presence of citrate have been carried out and the combined role of collagen and citrate in controlling mineral formation has been addressed for the first time. Through X-ray scattering and Atomic Force Microscopy characterizations on mineralized and non-mineralized collagen fibrils, we have found that citrate in synergy with collagen stabilizes an amorphous calcium phosphate (ACP) phase with platy morphology over one week and controls its deposition on collagen fibrils.